Análise de flexão de placas espessas através de métodos sem malhas com a utilização de uma técnica eficiente de integração - Konda, Danilo Hiroshi (2018)
In this work, we present the use of meshless methods for the analysis of the thick plate bending problem under consideration of Reissner's hypotheses. A new procedure for the evaluation of integrals that describe the problem is used to reduce the computational cost. The developed formulation is tested to evaluate the occurrence of the shear locking e ect when using the proposed integration scheme. Monomial bases of di erent ordens are used to analyze the shear locking e ect. Different shape functions are used to evaluate the MLPG method performance in the solution of plate bending problem. The formulation is also analyzed when using di erent processes of imposing essential boundary conditions. The results obtained with the MLPG considering the proposed integration scheme are compared with the results obtained with the MLPG considering the traditional integration process and also with results obtained from formulations that use the nite element method.